Existence and uniqueness of positive solutions for higher order nonlocal fractional differential equations - Zhang, Xinguang; Han, Y. (Elsevier, 2012)
By means of a monotone iterative technique, we establish the existence and uniqueness of the positive solutions for a class of higher conjugate-type fractional differential equation with one nonlocal term. In addition, the iterative sequences of solution and error estimation are also given. In particular, this model comes from economics, financial mathematics and other applied sciences, since the initial value of the iterative sequence can begin from an known function, this is simpler and helpful for computation.